Analysis of Emotional Aspects in Lyrics and Melody of the Traditional Song “Awe Jale” in Sentani Tribe - Kaiway, Yudhi Aji Ristanto; Ardini, Ni Wayan; Yudarta, I Gede (Journal of Music Science, Technology, and Industry, 2024)
Purpose: A traditional Sentani song named "Awe Jale" is one of the valuable cultural heritages of the Papuan people. In this study, an analysis of the emotional aspects contained in the lyrics and melody of the song was carried out. Research method: This research aims to understand how the lyrics and melody of "Awe Jale" communicate and influence the feelings of the listener. The analytical methods used include lyric text analysis, melody analysis, and integration of these two aspects to understand the overall emotional experience conveyed by the song. Results and discussion: The traditional song of the Sentani tribe "Awe Jale" is an embodiment of the rich culture and life of the Papuan people. Implication: Through emotion analysis of the lyrics and melody of this song, people can understand more deeply about the expression of feelings, cultural values, and the close relationship between humans and nature and spiritual life.